An ethnographic study of how health system, socio-cultural and individual factors influence uptake of intermittent preventive treatment of malaria in pregnancy with sulfadoxine-pyrimethamine in a Ghanaian context. - Matilda Aberese-Ako (Public Library of Science (PLoS), 2021)
Background Intermittent preventive treatment of malaria among pregnant women with sulfadoxine-pyrimethamine (IPTp-SP), is one of the three recommended interventions for the prevention of malaria in pregnancy (MiP) in sub-Sahara Africa. The World Health Organisation recommended in 2012 that SP be given at each scheduled ANC visit except during the first trimester and can be given a dose every month until the time of delivery, to ensure that a high proportion of women receive at least three doses of SP during pregnancy. Despite implementation of this policy, Ghana did not attain the target of 100% access to IPTp-SP by 2015. Additionally, negative outcomes of malaria infection in pregnancy are still recurring. This ethnographic study explored how health system, individual and socio-cultural factors influence IPTp-SP uptake in two Ghanaian regions. Methods The study design was ethnographic, employing non-participant observation, case studies and in depth interviews in 8 health facilities and 8 communities, from April 2018 to March 2019, in two Ghanaian regions. Recommended ethical procedures were observed. Results Health system factors such as organization of antenatal care (ANC) services and strategies employed by health workers to administer SP contributed to initial uptake. Women's trust in the health care system contributed to continued uptake. Inadequate information provided to women accessing ANC, stock-outs and fees charged for ANC services reduced access to IPTp-SP. Socio-cultural factor such as encouragement from social networks influenced utilization of ANC services and IPTp-SP uptake. Individual factors such as refusing to take SP, skipping ANC appointments and initiating ANC attendance late affected uptake. Conclusion Health system, socio-cultural and individual factors influence uptake of optimum doses of IPTp-SP. Consequently, interventions that aim at addressing IPTp-SP uptake should focus on regular and sufficient supply of SP to health facilities, effective implementation of free ANC, provision of appropriate and adequate information to women and community outreach programmes to encourage early and regular ANC visits.